2003
DOI: 10.2224/sbp.2003.31.5.523
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Kuwaiti and Egyptian Teachers in Type a Behavior and Job Satisfaction: A Cross-Cultural Study

Abstract: This study investigates the differences between males and females on the one hand, and between Egyptian and Kuwaiti teachers on the other. It also aims to examine the correlation between Type A behavior and job satisfaction. The sample consists of 406 teachers (109 females and 279 males; 253 Kuwaiti, 153 Egyptian). Tools used in this study are: Scales of Type Abehavior (Abdel-Khalek & Chukry, 1991), and job satisfaction (Cooper, Sloan, & Williams, 1998). Results reveal that there are no significant di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
2
0
2
Order By: Relevance
“…Carver and Glass (1978) found that “Type A Personality” has further two dimensions, which include success‐endeavor and impatience. Al‐Mashaan (2003) reported that “Type A Personality” exhibited high satisfaction with their job. The cause of low satisfaction is considered to be due to environmental factors.…”
Section: Intelligence Quotient Job Satisfaction and Job Performancementioning
confidence: 99%
“…Carver and Glass (1978) found that “Type A Personality” has further two dimensions, which include success‐endeavor and impatience. Al‐Mashaan (2003) reported that “Type A Personality” exhibited high satisfaction with their job. The cause of low satisfaction is considered to be due to environmental factors.…”
Section: Intelligence Quotient Job Satisfaction and Job Performancementioning
confidence: 99%
“…Del mismo modo, la investigación con profesores de países africanos mostró que los hombres estaban más satisfechos con algunos componentes de satisfacción laboral referentes a la estructura y los procesos organizacionales, ya que estos consideran que el sistema de promoción, recompensas e incentivos es más justo, además de que las escuelas permiten a los hombres mayor autonomía para usar sus habilidades (Al-Mashaan, 2003). Se hace evidente en las relaciones establecidas en el ámbito escolar que docentes varones, de acuerdo con la demanda de actividades que serán desempeñadas, tienden a presentar una mayor percepción de satisfacción en vista de la postura y la ocupación de los puestos de gestión.…”
Section: Discussionunclassified
“…De modo similar, investigação com professores de países africanos evidenciou que os homens estavam mais satisfeitos com alguns componentes da satisfação do trabalho referentes à estrutura e aos processos organizacionais, em virtude de estes considerarem mais justo o sistema de promoção, recompensas e incentivos, além de as escolas permitirem aos homens maior autonomia para o uso de suas habilidades (Al-Mashaan, 2003). Torna-se perceptível nas relações estabelecidas no cenário escolar, que professores do sexo masculino, de acordo com a demanda de atividades a serem desempenhadas, tendem a apresentar maior percepção de satisfação em vista da postura e da ocupação de cargos de gestão.…”
Section: Participantesunclassified